Implementasi Algoritma Sequential Search Pada Aplikasi Ensiklopedia Dermatologi berbasis Mobile - Agustina Srirahayu; Fajar Suryani (Universitas Duta Bangsa Surakarta, 2021)
Encyclopdia Dermatology contains various lists of skin diseases, of course terms that some people find difficult to understand. Search for the term skin disease in the essence of health can be done in this dermatology encyclopedia application, with search keywords for symptoms, skin rashes and location, as well as based on alphabetical order of the name of the skin disease. Search keywords can be written in the search field found in the Disease Menu. There are several types of search algorithms, one of which is the sequential search algorithm. Sequential search was chosen because this method performs sequential linear searches that compare keywords with elements that have been stored in the database. These elements are stored in the form of an array data. There are three stages in the process of the sequential search algorithm method until the search process is complete. The results of the research have been tested with the black box method where all activities are successful and successful according to the needs of the implemented application functionality.